Joint estimation of angler revealed preference site selection and stated preference choice experiment recreation data considering attribute non-attendance. Issue 1 (2nd January 2023) - Hindsley, Paul; Landry, Craig E.; Schnier, Kurt; Whitehead, John C.; Zarei, Mohammadreza
ABSTRACT: We estimate angler demand models with revealed preference (RP) and stated preference (SP) site selection marine recreational fishing data. We combine RP data from the Marine Recreational Information Program (MRIP) creel survey with SP discrete choice experiment survey data from 2003/2004. There are eight SP trip decisions and one RP trip decision for each of 1928 anglers who provided enough information to be analysed. Joint RP-SP generalized multinomial logit models are estimated. We find that the SP travel cost coefficient is much lower than the RP travel cost coefficient in absolute value, suggesting hypothetical bias in the SP data. This difference is reflected in the willingness to pay estimates, where the SP estimates for improved catch are much higher than the RP estimates. We use inferred attribute non-attendance (ANA) methods to identify respondents who may be ignoring the SP cost variable. The SP cost coefficient accounting for ANA is much higher in absolute value than the SP coefficient from the model that does not account for ANA. The ANA model indicates much more consistency between the RP and SP data. The smaller difference in the travel cost coefficients is also reflected in the willingness to pay estimates.